Metaverse Learning Environments and Student Well-Being: A Longitudinal Study on The Impact of Immersive Educational Counseling - Rais, Rinovian; Dwita, Alfiani; Rosidin, Rosidin; Sok, Vann (Yayasan Minang Darussalam, 2024)
This longitudinal study investigates the influence of immersive educational counseling within metaverse learning environments on student well-being. As educational institutions increasingly integrate virtual and augmented reality technologies, understanding their effects on students’ mental health and academic performance is essential. The research focuses on a diverse cohort of students who participated in immersive counseling sessions designed to enhance emotional support, social engagement, and academic guidance. Data collection spanned two academic years, utilizing quantitative surveys, qualitative interviews, and performance metrics to assess changes in well-being and academic outcomes.Results reveal that students engaged in metaverse counseling exhibited significant improvements in emotional resilience, motivation, and overall academic performance compared to their peers receiving traditional counseling. Additionally, the immersive nature of the metaverse fostered a sense of community and belonging, which further contributed to enhanced well-being. This study underscores the transformative potential of metaverse environments in educational settings, advocating for the incorporation of innovative technologies to support student mental health and academic success.